Conservation of Ephestia kuehniella eggs as hosts for Trichogramma ostriniae. (20th April 2015) - St‐Onge, M.; Cormier, D.; Todorova, S.; Lucas, É.
Abstract: Mass rearing of numerous biological control agents depends on large amounts of factitious hosts like Ephestia kuehniella eggs. Moreover, production of some parasitoids, such as Trichogramma, requires hosts of high quality. The objective of this study was to determine the optimal conservation method that allows E. kuehniella eggs to remain suitable for parasitism and development of Trichogramma ostriniae for the longest period of time. Fifteen sterilization–conservation treatments were compared: nine consisting of submersion of the eggs in liquid nitrogen as a conservation mode, two consisting of sterilization of the eggs with UV and four consisting of sterilization with freezing at −15°C. Liquid nitrogen submersion of E. kuehniella eggs did not allow the production of T. ostriniae . The sterilization by exposition to UV light followed by conservation using vacuum packing and refrigeration at 4°C provided the longest conservation of E. kuehniella eggs for T. ostriniae rearing. It was the only treatment (75.4 ± 4.62%) for which the parasitism rate remained over 70% after 2 weeks.